External Linkages and Economic Growth in Colombia : Insights from A Bayesian VAR Model - Osterholm, Par (IMF Working Papers; Working Paper, 2008)
This paper investigates the sensitivity of Colombian GDP growth to the surroundingmacroeconomic environment. We estimate a Bayesian VAR model with informative steady-statepriors for the Colombian economy using quarterly data from 1995 to 2007. A variancedecomposition shows that world GDP growth and government spending are the most importantfactors, explaining roughly 17 and 16 percent of the variance in Colombian GDP growthrespectively. The model, which is shown to forecast well out-of-sample, can also be used toanalyse alternative scenarios. Generating both endogenous and conditional forecasts, we showthat the impact on Colombian GDP growth of a substantial downturn in world GDP growthwould be non-negligible but still a mild decline by historical standards.